Strategi Guru dalam Meningkatkan Budaya Literasi Digital Siswa pada Mata Pelajaran Pendidikan Agama Islam - Eka Mustika Riantina; Dede Tri Irawan; Islamiyah Islamiyah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze teachers' strategies in improving students' digital literacy culture in Islamic Religious Education classes at SMK Negeri 4 Ogan Komering Ulu. The research employed a qualitative field research approach. The participants consisted of the principal, vice principal for curriculum, Islamic Religious Education teachers, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and analyzed using an interactive model involving data condensation, data display, and conclusion drawing. Data trustworthiness was ensured through source triangulation, method triangulation, and member checking. The findings reveal that teachers fostered students' digital literacy culture through digital literacy-based lesson planning, the integration of digital learning media, the habituation of reading digital learning resources, and technology-based learning assignments. The effectiveness of these strategies was supported by strong school commitment, collaboration among teachers, parental involvement, and the availability of digital learning facilities. Meanwhile, the main obstacles included students' low reading interest, the tendency to use digital devices primarily for entertainment, limited technological facilities, and varying levels of students' digital competence. The study concludes that strengthening digital literacy culture in Islamic Religious Education not only enhances students' digital competencies but also promotes critical thinking, responsible digital behavior, and religious character development in responding to the challenges of the digital era.